2015
DOI: 10.2217/rme.15.49
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Wharton’s Jelly and Cord Blood as a Source of Mesenchymal Stem Cells for Diabetes Cell Therapy

Abstract: Wharton's jelly was more homogeneous, can better differentiate into insulin producing cells in vitro and better control hyperglycemia in diabetic rats in vivo, as compared with UCB. These results indicate that WJ-MSCs represent a potential source of cells in the field of diabetes mellitus cell therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…As such, the best current practice for treating diabetes involves transplantation of the islet or pancreas [3–5], but the large numbers of patients, limited supply of donor tissue, the risk and cost of operation, and necessity for lifelong immunosuppression have limited the application of this treatment modality. β -like cells differentiated from embryonic stem cells (ES) [6], induced pluripotent stem cells (iPSCs) [7], and mesenchymal stem cells (MSC) [8] have become the most promising solution by providing a potentially inexhaustible means of generating β cells for transplantation and with low immunogenicity. Recently, Alipio et al successfully induced iPSCs to differentiate into β -like cells [9].…”
Section: Introductionmentioning
confidence: 99%
“…As such, the best current practice for treating diabetes involves transplantation of the islet or pancreas [3–5], but the large numbers of patients, limited supply of donor tissue, the risk and cost of operation, and necessity for lifelong immunosuppression have limited the application of this treatment modality. β -like cells differentiated from embryonic stem cells (ES) [6], induced pluripotent stem cells (iPSCs) [7], and mesenchymal stem cells (MSC) [8] have become the most promising solution by providing a potentially inexhaustible means of generating β cells for transplantation and with low immunogenicity. Recently, Alipio et al successfully induced iPSCs to differentiate into β -like cells [9].…”
Section: Introductionmentioning
confidence: 99%
“…Autologous bone marrow MSCs, with the ability of homing to the target, perception of injury signals, migration to the injured site, proliferation, and differentiation, participate in tissue injury repair, achieving effective results [ 3 6 ]. MSCs can be obtained from mature bone marrow, fatty tissues, placenta, scalp, pancreatic tissue, endometrium, Wharton's jelly, and umbilical cord blood [ 7 14 ]. Under different induction conditions, MSCs can differentiate into bone, cartilage, fat, muscle, tendon, and other mesodermal cells, but also cross mesoderm differentiation, forming various ectodermal cells (e.g., neurons, gliacytes, and skin cells) and endodermal or vascular endothelial cells (e.g., liver and kidney cells) [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, MSCs from hUCB and WJ differ in their functional properties. El Demerdash et al found that WJ-derived MSCs could better differentiate into insulin producing cells in vitro and better controlled hyperglycemia in diabetic rats in vivo [8]. The differential influence of clinical variables on the cytokine and chemokine secretome and the neuronal differentiation of WJ-derived MSCs compared with hUCB-derived MSCs is unknown.…”
mentioning
confidence: 99%